2020
DOI: 10.1371/journal.pntd.0007466
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya outbreak in Bangladesh (2017): Clinical and hematological findings

Abstract: Introduction A massive outbreak of chikungunya virus (CHIKV) occurred in Bangladesh during the period of April-September 2017, and over two million people were at risk of getting infected by the virus. A prospective cohort of viremic patients was constituted and analyzed to define the clinical, hematological, and long-term aspects of this outbreak. Methods A 35-day long comprehensive survey was conducted in two major, neighboring cities, Dhaka and Mymensingh. One-hundred and eighty-seven laboratory-confirmed C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
3
24
0
2
Order By: Relevance
“…This new sub-lineage caused the largest CHIKV outbreak in 2017. More than one thousand confirmed cases were reported in Dhaka city, and numbers of cases peaked in July during the monsoon season [ 56 , 57 ]. Although Ae.…”
Section: Discussionmentioning
confidence: 99%
“…This new sub-lineage caused the largest CHIKV outbreak in 2017. More than one thousand confirmed cases were reported in Dhaka city, and numbers of cases peaked in July during the monsoon season [ 56 , 57 ]. Although Ae.…”
Section: Discussionmentioning
confidence: 99%
“…14 Overall,24.4% of children were reportedly affected during the 2019 outbreak in the Maldives, and in our cohort, we observed 20% with confirmed infection, compared with 17% of children reportedly affected in an outbreak on the Indian subcontinent. 25,39 These data indicate that the approximate proportion of children affected during outbreaks is generally less than one-fourth of all cases. We also observed similarity between the mean age of children affected in our cohort and data reported regarding an outbreak in South America.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, arthritogenic manifestations are reportedly much less common in children than in adults. 39 This might be due to the robust nature of the immune system of children, which enables more rapid clearance of the infection. 44 Febrile exanthema is a challenge for clinicians because a wide range of viral and bacterial infections can produce a rash.…”
Section: Discussionmentioning
confidence: 99%
“…In children reported rash on face, hands and legs. Several studies reported that, the fever lasts from several days up to a week is about 76-100 % of symptomatic patients, it can be continuous or intermittent with mild fever [14, 15, 16, 17, 18].The headache, muscular pain, and joint pain of both upper and lower limbs were reported in previous studies associated by chikungunya infection [19,12].…”
Section: Symptoms and Clinical Featuresmentioning
confidence: 99%
“…In adult patients (25-60 years) were suffering myalgia accompanied by arthralgia after 3 days of infection (table 1). The previously published reports have indicated that the combination of fever and severe arthralgia (present in more than 95% of cases) [12,13]. Other clinical manifestations reported as, headache, joint pain, redness of joints , swelling of joints vomiting and fatigue for 3 to 5 days.…”
Section: Symptoms and Clinical Featuresmentioning
confidence: 99%